Analysis of the fatigue crack initiation of a wind turbine gear considering load sequence effect. (February 2020) - He, Haifeng; Liu, Huaiju; Zhu, Caichao; Wei, Peitang; Tang, Jinyuan
Under the action of the wind, wind turbine gears experience complex loading histories in which the amplitude of the load is varying. The variable load conditions make the load sequence and the load amplitude inverse number as important factors to be considered for gear fatigue analysis. In the present work, a damage-coupled elastic-plastic constitutive model based on the continuous damage mechanics (CDM) is established to analyze the influence of load sequence on rolling contact fatigue (RCF) crack initiation of a wind turbine gear. The crack initiation is indicated by reaching the critical threshold of the defined damage variable related to the shear stress range and the plastic strain. During repeated loading cycles, the deterioration of material is reflected by gradually reducing mechanical properties. The numerical simulation is carried out in the frame of ABAQUS using the subroutine of user defined material subroutine (UMAT). The two-level load conditions are selected and results of which are compared with those of constant amplitude load conditions. Different inverse numbers are utilized to investigate the influence of load amplitude inverse number on crack initiation life. Simulation results are compared with existing damage accumulation criteria. The results indicate that when the first crack initiates, the sum of lifetime ratio is greater than unity for the low-high load sequence, while this value is less than unity for the high-low load sequence. Furthermore, the increase of the load amplitude inverse number will weaken the influence of the load sequence with regard to the crack initiation life. The highly nonlinear characteristic of damage accumulation during fatigue process under variable loading histories is captured by the proposed method. This method provides a new way to reveal the contact fatigue process of gears under variable loading histories and lay a foundation for predicting the accurate fatigue life under the real, complex loading condition of a gear.